Body Image and Social Media: A Qualitative Investigation of the Influence of Instagram on Young Women’s Self-Perception and Body Satisfaction - Sattarpanahi, Elham; Leila kiani; Hesami, Shabnam; Salehi, Nasrin; Kavousighafi, Mohammad (Psychology of Woman Journal, 2024)
Objective: This study aimed to qualitatively investigate the influence of Instagram on young women’s self-perception and body satisfaction, exploring the complex dynamics between social media interactions and their impacts on body image and self-esteem. Methods and Materials: Utilizing a qualitative research design, this study conducted semi-structured interviews with 27 young women aged 18 to 29, who were regular Instagram users. The interviews focused on participants’ Instagram usage patterns, their exposure to body image-related content, and the effects of these interactions on their self-perception and body satisfaction. Thematic analysis was employed to identify and analyze patterns within the data, with theoretical saturation guiding the depth and comprehensiveness of the investigation. Findings: The analysis revealed seven main themes: Impact of Instagram on Self-Perception, Influence of Visual Content, Social Comparison Dynamics, Psychological Outcomes, Navigating Online Spaces, Regulation and Policy, and Technological Influences. These themes encompassed various categories and concepts, such as self-esteem fluctuations, identity shaping, body image concerns, exposure to beauty standards, content consumption patterns, upward vs. downward comparison, emotional and cognitive responses, behavioral changes, strategies for digital literacy, and the need for platform accountability. Conclusion: The study concludes that Instagram significantly influences young women’s self-perception and body satisfaction, with social comparison dynamics, exposure to idealized beauty standards, and the nature of content consumption playing pivotal roles. While Instagram offers opportunities for positive engagement and support, it also poses challenges to body image and self-esteem. Addressing these impacts requires a multifaceted approach, including enhanced digital literacy, critical engagement with social media content, and proactive measures by social media platforms to foster a healthier online environment.